Efek Curing Air Laut Terhadap Kuat Tekan Beton Mutu Tinggi Yang Menggunakan Fly Ash Sebagai Subtitusi Pasir - Azhari Zahlim; Erniati Bachtiar; Ritnawati Makbul (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2022)
Fly ash waste accumulates from year to year at PLTU in South Sulawesi. The potential of fly ash as an environmentally friendly material to be used as a cement substitute is significant, either partially or entirely. This research aims to analyze the corelation between fly ash substitution as sand substitution and the compressive strength of high-strength concrete treated in seawater and freshwater. Researchers made samples of high-strength concrete with variations in the percentage of fly ash and variations in treatment. Variations in the percentage of fly ash as substitution of sand are 0%, 10%, 20%, and 30%, and variations in curing using fresh water and seawater. Sample treatment was carried out for up to 28 days, after which the compressive strength test according to the Indonesian National Standard (SNI) was carried out. The study results show that the relationship between fly ash substitution and a sand substitution on the compressive strength has a significant correlation. The higher the percentage of fly ash, the higher the compressive strength of the concrete, both fresh and seawater curing. Besides that, the compressive strength of high-strength concrete with freshwater curing treatment is greater than the seawater curing treatment.